History, philosophy, culture : revisiting Professor G.C. Pande's thoughts and works - Bhattacharya, Sibesh Chandra (New Delhi : Aryan Books International, 2010)
Contributed articles.
Keywords: Pande, Govind Chandra, -- 1923-; Philosophy, Indic; India -- Civilization